1983
DOI: 10.1099/00221287-129-8-2649
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Taxonomy of Moderately Halophilic Gram-negative Bacteria from Hypersaline Soils

Abstract: A total of 132 moderately halophilic bacteria were isolated from hypersaline soils with a C1-content between 2-36 and 12.72% (w/v) located near Alicante (S.E. Spain) and examined for 98 phenotypic characteristics including their response to cytological, physiological, biochemical and nutritional tests. They were submitted to a numerical analysis together with six reference strains using both simple matching (SsM) and Jaccard (S,) coefficients, and cluster analysis was carried out by the unweighted pair group m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 17 publications
1
51
0
1
Order By: Relevance
“…For example, to test acid production from sugars, we used two different culture media: Leifson medium, with a low peptone and high carbohydrate content (LEIFSON, 1963), and MH basal medium (QUESADA et al, 1983), which had more peptones and a lower carbohydrate content. In this way our results indicated that H. elongata was not able to ferment glucose, just as other authors such as VENTOSA et al (1998) have also observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, to test acid production from sugars, we used two different culture media: Leifson medium, with a low peptone and high carbohydrate content (LEIFSON, 1963), and MH basal medium (QUESADA et al, 1983), which had more peptones and a lower carbohydrate content. In this way our results indicated that H. elongata was not able to ferment glucose, just as other authors such as VENTOSA et al (1998) have also observed.…”
Section: Discussionmentioning
confidence: 99%
“…MH medium (QUESADA et al, 1983) with 7.5% (w/v) sea-salt solution (RODRÍGUEZ-VALERA et al, 1981) was used to maintain the strains, to prepare the inocula and as the basal medium for phenotypic tests, unless otherwise stated. The pH was adjusted to 7.2 with 1M NaOH except for the media used for growing H. magadiensis and H. campisalis, which were adjusted to pH 9.…”
Section: Maintenance and Basal Mediummentioning
confidence: 99%
“…All these moderate halophilic species belong to the low G+C group of the gram-positive phylum, only Nesterenkonia (formerly Micrococcus halobius) is within the high G+C group (Mota et al, 1997;Stackebrandt et al, 1995). Saline soils appear to yield mostly halotolerant rather than halophilic microorganisms, presumably reflecting adaptation to periodic edisodes of relatively high dilution (Quesada et al, 1982(Quesada et al, , 1983. Saline soils have been somewhat neglected as compared to hypersaline aquatic environments.…”
Section: Distribution Of Actinomycetes In Hypersaline Soilsmentioning
confidence: 99%
“…Growth under anaerobic conditions was determined on MA and in MB supplemented with 5 % (w/v) NaCl and with or without 0.5 % (w/v) glucose or 0.1 % (w/v) nitrate, by using the GasPak Anaerobic System (BBL) according to the manufacturer's instructions. Oxidation/fermentation of glucose and respiration on fumarate, nitrate and nitrite were studied according to the procedures described by Mata et al (2002) by using MH medium (Quesada et al, 1983) with 7.5 % sea salts solution (Rodriguez-Valera et al, 1981) as the basal medium. Nutritional tests were performed by using classical methods (Ventosa et al, 1982) in modified Koser medium (Koser, 1923) [containing (l 21 ): 50 g NaCl, 2 g KCl, 0.2 g MgSO 4 .…”
Section: Institute Of Medicinal Biotechnology Chinese Academy Of Medmentioning
confidence: 99%